Cell mediated immune response of the Mediterranean sea urchin Paracentrotus lividus after PAMPs stimulation. (September 2016) - Romero, A.; Novoa, B.; Figueras, A.
Abstract: The Mediterranean sea urchin ( Paracentrotus lividus ) is of great ecological and economic importance for the European aquaculture. Yet, most of the studies regarding echinoderm's immunological defense mechanisms reported so far have used the sea urchin Strongylocentrotus purpuratus as a model, and information on the immunological defense mechanisms of Paracentrotus lividus and other sea urchins, is scarce. To remedy this gap in information, in this study, flow cytometry was used to evaluate several cellular immune mechanisms, such as phagocytosis, cell cooperation, and ROS production in P. lividus coelomocytes after PAMP stimulation. Two cell populations were described. Of the two, the amoeboid-phagocytes were responsible for the phagocytosis and ROS production. Cooperation between amoeboid-phagocytes and non-adherent cells resulted in an increased phagocytic response. Stimulation with several PAMPs modified the phagocytic activity and the production of ROS. The premise that the coelomocytes were activated by the bacterial components was confirmed by the expression levels of two cell mediated immune genes: LPS-Induced TNF-alpha Factor (LITAF) and macrophage migration inhibitory factor (MIF). These results have helped us understand the cellular immune mechanisms in P. lividus and their modulation after PAMP stimulation. Highlights: Two cell populations were described by flow cytometry in Paracentrotus lividus . The amoeboid-phagocytes were responsible for the phagocytosis and ROS production. Cooperation between cells and humoral components increased the phagocytic response. Stimulation with PAMPs modified the phagocytic activity and the production of ROS. The expression levels of LITAF and MIF genes were modulated after PAMP stimulation.